Comparison of Anthropometric Indices of 10-16 Years Old School Girls with the NCHS International Standard - Sajad Arshadi; Mahbobeh Dehghan (Islamic Azad University, 2018)
Introduction: One of the most important international indicators for assessing growth and physical health is measuring weight, height, BMI and other parameters of growth and development and comparing it with standard curves. Accordingly, the purpose of this study was to compare anthropometric indices of 10- 16 years old school girls with the NCHS iternational standard. Methods: In this descriptive cross-sectional study, 267 female students aged 10 to 16 year-old in Taft city were randomly selected through cluster sampling and the mean and standard deviation of their anthropometric indices in their age ranges with related methods were measured and compared to the National Center for Health Statistics (NCHS) standard. Finally, the data were analyzed using both descriptive and inferential statistics including Kolmogrov- Smirnov and single sample t-test at a significance level of less than 0.05. Results: The results showed that weight, triceps skinfold thickness, subscapular skinfold thickness of students in all age ranges were significantly lower than NCHS standard (p ≤0.05). But the height, body mass index, mid arm circumference, waist circumference, upper leg length and upper arm length of students in some age groups were significantly lower than the NCHS standard (P ≤0.05), and in other age groups, there was no significant difference (P≥ 0.05). Conclusion: The results of this study showed that the anthropometric characteristics of these students are less than international standards. Significant changes made in some of these anthropometric indices can be due to the geographical, climatic, nutritional and physical activity of students, which should be given more attention.